Pengaruh Thin Capitalization, Intensitas Modal Terhadap Tax Avoidance : Pada Indeks Infobank15 Tahun 2018-2020 - Abigail Cantika Nainggolan; Francis Hutabarat (Jurnal Ilmiah Mahasiswa Manajemen, Bisnis dan Akuntansi (JIMMBA), 2022)
This study aims to examine the effect of thin capitalization, capital intensity and profitability on tax avoidance in banking sector companies listed in the 2018-2020 infobank15. This study uses a sample of 15 companies with secondary data taken from the financial statements of the banking sector. companies listed on infobank15 in 2018-2020 with a sample of 45. This study uses descriptive analysis, linear regression interpretation, significant test and coefficient of determination. The results of this study indicate that thin capitalization in banking sector companies has no significant effect on tax avoidance. While the capital intensity and profitability have a significant effect on tax avoidance.